Decolonizing Management, Spirituality, and Religion: New Paradigms for Inclusive Scholarship - Jeong, Sunny (Journal of management, spirituality & religion, 2025)
This special issue presents a collection of papers that make distinctions between decolonization and decoloniality and their impact on how spirituality is introduced in management research. While decolonization focuses on undoing the political and economic effects of colonialism, decoloniality is concerned with addressing the deeper cultural and epistemological issues that underlie systems of colonialism influence. This research emphasis on decoloniality seeks to challenge and transform the resulting systems of social inequity while addressing the ongoing cultural and epistemological influences that continue to shape our understanding of elemental vs. divine spirituality. In this issue, we present scholarly works that explore the challenges of colonial influence in race, gender, class, and culture, and in our foundational understanding of workplace spirituality. The anticipated outcome of this research is to highlight the intended role of spirituality and religion in fostering ethical, humane, and sustainable management practices.